Correlação entre o estado nutricional, capacidade funcional e presença desarcopenia em idosos atendidos em um hospital de ensino - MOREIRA, Jorvana Stanislav Brasil (2023)
Sarcopenia is the process of continuous loss of agerelated muscle mass, which can affect or be influenced by nutritional status, as well as predisposing functional limitation in the elderly due to the impairment of physical qualities necessary for the performance of basic activities of daily living. In this study, the investigation of this process is based on the objective of correlating nutritional status and functional capacity with the presence of sarcopenia in the elderly. For this purpose, a crosssectional study was carried out with 156 elderly people treated at the outpatient clinic of a teaching hospital. The criteria of the Euroepan Working Group on Sarcopenia in Older Persons were used to verify sarcopenia. Sociodemographic data were collected using a questionnaire, nutritional status assessed using the Mini Nutritional Assessment, and functional capacity assessed using the Katz index. Descriptive statistical analyses and correlation between variables were applied, and the significance alpha level of 5% (p ≤0.05) was adopted. The prevalence of sarcopenia was 19.9% (n=31). The elderly had nutritional status classified as normal (79.5%, n=124) and were independent (98.1%, n=153). The results showed correlation of sarcopenia with age (p=0.0004, r=0.2), body mass index (p<0.0001, r= 0.3), arm circumference (p=0.0005, r= 0.2), and with calf circumference (p=<0.0001, r=0.4). There were no significant results between sarcopenia correlation with nutritional status and functional capacity (p>0.05).